ANALISIS PENGEMBANGAN KARYAWAN PADA POJOK CAFFE & RESTO - Lilis Fitriyani; Puji Isyanto; Dini Yani (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to analyze development needs, explain the methods used in development activities, explain the benefits of development, inhibiting factors and evaluation methods. Employees at the corner cafe & restaurant business. Employee development has important uses in increasing the motivation, personality and abilities of employees. There are several obstacles that arise, namely the lack of funds, attention from the owner/manager and adequate facilities. This research was conducted using observation and interview methods with the owner/manager and several employees. This study uses a descriptive analysis method with a qualitative approach. The results of the study show that the employee development program at the cafe & restaurant corner is carried out based on the needs of employees using two methods, namely instruction and mentoring, for evaluation it is carried out by sharing between employees and the owner. The benefits of development are fully supported by Corner Cafe & Restaurant. Pojok caffe & restaurant should provide a special and further employee development program and evaluation of development activities must be carried out formally.